Crystal structure of benzyltrichloridobis(1H-pyrazole-κ2N)tin(IV), C13H15Cl3N4Sn - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (de Gruyter, 2019)
C13H15Cl3N4Sn, monoclinic, C2/c (no. 15), a = 32.4593(4) Å, b = 7.43400(10) Å, c = 14.7108(2) Å, β = 106.084(1)°, V = 3410.80(8) Å3, Z = 8, Rgt(F) = 0.0151, wRref(F2) = 0.0410,T = 293(2) K. CCDC no.: 1902318 The molecular structure is shown in the figure. Table 1 contains crystallographic data and Table 2 contains the list of the atoms including atomic coordinates and displacement parameters.